THE ISSUES OF RELIABILITY AND DURABILITY OF REINFORCED CONCRETE HIGHWAY BRIDGES - Savchynskyi, B. V. (Science and Transport Progress, 2006)
The basic criteria for assessing reliability and durability of ferrоconcrete road bridges are generalized. Recommendations for increasing reliability and durability of such bridges have been given.